The Relation of the Law on Marriage of the Batak Indigenous Clan with the Incest Marriage Law - Ginny Mega Maulidia Hasibuan (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
A clan marriage is a marriage between representatives of the same ethnic group and clan. In general, the Batak community expressly prohibits the marriage of a clan because this marriage is considered a blood marriage, this is a customary rule that must be obeyed by the community in order to avoid various sanctions and customary punishments that apply. Therefore, parents must inform their children as the next generation that the marriage of one clan is prohibited by the prevailing customary provisions. Until now the prohibition of marriage of one clan has been preserved by the Batak community. The purpose of this study was to determine the concept of kinship between a group of Batak people as a general concept of kinship and the legal consequences of a Semarga marriage. In addition, those who violate the prohibition are correct and relevant to be given social punishment, this provision is also related to Law no. 1 of 1974 which is the unification of the Marriage Law which according to general rules applies to marriages in Indonesia. This investigation is a form of empirical legal investigation, including legal identification and investigation of results. Legal normative approach using descriptive-analytic method is the research method used in this study.